Sistem Informasi Anggaran pada PT. Ardhi Karya Teknik - Uus Rusmawan; Safarin Novarizal (Jurnal Jaring SainTek, 2021)
Ardhi Karya Teknik is a company engaged in construction, painting, cooling engineering and information technology. This company experiences difficulties in managing finances, especially in terms of budget provision and use, the concentration of problems revolves around the budget allocation for operational costs that are routinely issued every year and the facts in the field regarding the use of the budget. Therefore it is necessary to have a budget application that is able to manage and provide accurate information about the company budget. The method used in this research is waterfall. After the application is made and implemented in the company, the budget allocation process and reports on its use can be presented quickly and accurately and can help the parties involved in the company to make the necessary decisions.